Eco-Heutagogy Based History Learning Design at Adiwiyata High School Bandung - M. Ari Kutowo; Muhammad Akhyar; Akhmad Arif Musadad (Universitas Negeri Semarang, 2026)
This study aims to develop a history learning design based on Eco-Heutagogy at SMA Adiwiyata Bandung as an innovative effort in integrating ecological awareness, learning independence, and strengthening student character through contextual and transformative history learning. The initial design of the learning device is compiled theoretically and conceptually based on the results of preliminary studies, needs analysis, theoretical studies, student characteristics, Adiwiyata school characteristics, and a synthesis of the concepts of eco-heutagogy and learning independence. The Eco-Heutagogy approach emphasizes student-centered learning (self-determined learning), reflective, collaborative, and based on harmonious relations between humans, the environment, and socio-cultural values. This study uses the Research and Development (R&D) method with stages including needs analysis, learning design design, initial product development, expert validation, limited trials, product revision, field trials, and model refinement. The research subjects involved history teachers and students at SMA Adiwiyata Bandung. Data collection techniques were conducted through interviews, observations, questionnaires, documentation studies, and learning outcome tests. While data analysis was conducted qualitatively and quantitatively to assess the feasibility, practicality, and effectiveness of the developed design. The results of the study indicate that the developed Eco-Heutagogy-based history learning design is theoretically and empirically valid, practical for use by teachers, and effective in increasing ecological awareness, critical thinking skills, learning independence, and active student involvement in the history learning process. Thus, this learning design has the potential to be a relevant alternative model to be implemented in environmentally conscious schools, Adiwiyata High School, to support the creation of history education that is meaningful, contextual, and oriented towards sustainable character building.